Abscysic acid and compatibility of atemoya (Annona x atemoya Mabb.) grafted onto native species - Baron, Daniel; Gimenez, Juliana Iassia [UNESP]; Ferreira, Gisela [UNESP] (Soc Brasileira Fruticultura, 2018)
Grafting is an effective technique used in the cultivation of commercial fruit species given the necessity to guarantee the genetic characteristics of productive species using selected clones. Although grafting is a common and widespread technique and phytohormones play a key role in the formation of tissues, the relationship between phytohormones, such as abscisic acid, and mechanisms of incompatibility is not yet well elucidated. Thus, the objective of this study was to establish whether a correlation exists between variations in abscisic acid and the compatibility of the atemoya (Annona x atemoya Mabb.) cultivar 'Thompson' grafted onto biriba [Annona mucosa (Bail.) H. Rainer], araticum-mirim [Annona emarginata (Schltdl.) H. Rainer 'var. mirim'] and araticum-de-terra-fria [Annona emarginata (Schltdl.) H. Rainer 'var. terra-fria']. Plant cultivation was carried out at the Botany Department of Instituto de Biociencias (IB), Unesp, Botucatu, Sao Paulo, Brazil. The plant material of grafted plants (stem above the grafted area, stem containing the grafted region, and stem below the grafted region) and ungrafted plants (stem 20 cm above ground) was collected 500 days after grafting (DAG) for the extraction and quantification of abscisic acid. The results of this study show that ungrafted Annona plants exhibit variations in the concentration of abscisic acid among the native rootstock species. When grafted, the most commonly used grafting combinations, araticum-de-terra-fria and araticum-mirim, present the same concentrations of abscisic acid in the graft region as self-grafted atemoya. It was concluded that the observed variations in the concentrations of abscisic acid in the graft region did not cause incompatibility in the combinations of atemoya grafted onto different native species.
Keywords: phytohormones; rootstock; post-grafting plant restoration